Wearable Technologies - Hamilton Ortiz, Jesús (IntechOpen, 2018)
This edited volume Wearable Technologies is a collection of reviewed and relevant research chapters, offering a comprehensive overview of recent developments in the field of computer engineering. The book comprises single chapters authored by various researchers and edited by an expert active in the computer engineering research area. All chapters are complete in themselves but united under a common research study topic. This publication aims at providing a thorough overview of the latest research efforts.